Ultrasensitive DNA Immune Repertoire Sequencing Using Unique Molecular Identifiers. (20th August 2020) - Johansson, Gustav; Kaltak, Melita; Rîmniceanu, Cristiana; Singh, Avadhesh K; Lycke, Jan; Malmeström, Clas; Hühn, Michael; Vaarala, Outi; Cardell, Susanna; Ståhlberg, Anders
Abstract: Background: Immune repertoire sequencing of the T-cell receptor can identify clonotypes that have expanded as a result of antigen recognition or hematological malignancies. However, current sequencing protocols display limitations with nonuniform amplification and polymerase-induced errors during sequencing. Here, we developed a sequencing method that overcame these issues and applied it to γδ T cells, a cell type that plays a unique role in immunity, autoimmunity, homeostasis of intestine, skin, adipose tissue, and cancer biology. Methods: The ultrasensitive immune repertoire sequencing method used PCR-introduced unique molecular identifiers. We constructed a 32-panel assay that captured the full diversity of the recombined T-cell receptor delta loci in γδ T cells. The protocol was validated on synthetic reference molecules and blood samples of healthy individuals. Results: The 32-panel assay displayed wide dynamic range, high reproducibility, and analytical sensitivity with single-nucleotide resolution. The method corrected for sequencing-depended quantification bias and polymerase-induced errors and could be applied to both enriched and nonenriched cells. Healthy donors displayed oligoclonal expansion of γδ T cells and similar frequencies of clonotypes were detected in both enrichment and nonenriched samples. Conclusions: Ultrasensitive immune repertoire sequencing strategy enables quantification of individual and specific clonotypes in a background that can be applied to clinical as well as basic application areas. Our approach is simple, flexible, and can easily be implemented in any molecular laboratory.